ZANZIBARIS OR AMAKHUWA? SUFI NETWORKS IN SOUTH AFRICA, MOZAMBIQUE, AND THE INDIAN OCEAN*. (29th May 2014) - Kaarsholm, Preben
Abstract This article investigates the role of Sufi networks in keeping Durban's 'Zanzibari' community of African Muslims together and developing their response to social change and political developments from the 1950s to the post-apartheid period. It focuses on the importance of religion in giving meaning to notions of community, and discusses the importance of the Makua language in maintaining links with northern Mozambique and framing understandings of Islam. The transmission of ritual practices of the Rifaiyya, Qadiriyya, and Shadhiliyya Sufi brotherhoods is highlighted, as is the significance of Maputo as a node for such linkages. The article discusses change over time in notions of cosmopolitanism, diaspora, and belonging, and examines new types of interactions after 1994 between people identifying themselves as Amakhuwa in Durban and Mozambique.